Low-content PcBN grade with high metal content in the binder
Patent Information
- Application Number
- JP2024570671
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-05-31
- Filing Date
- 2023-05-16
- Publication Date
- 2026-10-22
- Estimated Expiration
- 2043-05-16
Smart Images

Figure 0007940042000002 
Figure 0007940042000003 
Figure 0007940042000004
Abstract
Description
Technical Field
[0001] The present disclosure relates to polycrystalline cubic boron nitride (PcBN) compositions having ceramic binders with high metal content. The present application further relates to sintered PcBN compacts comprising the PcBN compositions, cutting tools, and related methods of producing the compacts.
Background Art
[0002] Cubic boron nitride (cBN) is a superabrasive hard material that is often associated with the formation of BN compacts for cutting and / or machining applications. Certain ceramic materials such as alumina (Al2O3), titanium nitride (TiN), titanium carbide (TiC), titanium carbonitride (TiCN), and silicon nitride (Si3N4) can be blended with cBN and further processed to improve the physical wear and crack resistance of cBN. However, such ceramic materials may not have sufficient fracture toughness, hardness, and / or heat resistance to function optimally when machining hard materials. Furthermore, existing PcBN-based compacts used to manufacture cutting tools may still exhibit rapid wear and cracking, followed by subsequent chipping.
[0003] In turning hard parts, improved fracture toughness is particularly necessary to prevent tool fracture during intermittent cutting. Unreacted tungsten carbide (WC) particles generated during grinding can act as crack propagation pathways. Conventional PcBN molded bodies containing one or more of quasi-stoichiometric (ss)TiN, TiCN, AlN, and Al2O3 typically have a sintered structure consisting of cBN particles, a ceramic-bonded phase composed of TiN and TiCN particles, and Al2O3 embedded and fixed in the TiN and TiCN ceramic-bonded phase matrix. Al2O3 is generally found as small, isolated spots within the TiN and TiCN ceramic-bonded phase matrix, or sometimes adjacent to cBN particles. Small white WC-Co islands or particles are often also visible in the microstructure. These usually exist as by-products of the grinding, known in metallurgical techniques as mill debris. Fracture toughness can be increased by chemically converting the WC mill debris into a tougher phase through a reaction with added Co. Nevertheless, a good ceramic binder phase plays a crucial role in achieving consistent, operable performance, and typically, the ceramic binder needs to be actively ground to reach the optimal target particle size.
[0004] To produce PcBN material used in tool manufacturing, cBN powder can typically be mixed with a ceramic binder substrate by first forming a pulverized slurry composition of mixed components with a grinding liquid (e.g., water, solvent, alcohol, or any mixture thereof). Subsequently, the composition is generally mixed for several hours, for example, in a ball mill, attritor mill, or planetary mill, to form a pulverized slurry blend.
[0005] The pulverized slurry blend may then be subjected to, for example, vacuum drying, air drying, freeze drying, or spray drying, and the powder blend then undergoes high-pressure, high-temperature (HPHT) sintering solidification.
[0006] The central motivation for the grinding operation is to promote a good ceramic binder distribution and good wettability between the cBN powder and the ceramic binder powder components. Importantly, adjusting the mixture components to suit the grinding operation is fundamental and key to enhancing the physical integrity of the ground components.
[0007] Desirable ceramic binder distribution and good wettability are essential parameters for obtaining PcBN-based tools that do not fracture when cutting or machining ferrous metals, for example. A drawback is that if the ceramic binder distribution and wettability are significantly below standard and quality, porosity and cracking may unnecessarily occur as a result of the susceptibility of the final sintered PcBN body, which is detrimental to the manufactured PcBN molded body.
[0008] Therefore, taking the above into consideration, there is a need for PcBN compositions with enhanced physical properties to manufacture robust, high-quality tools with excellent performance for cutting and machining difficult-to-machine materials. [Overview of the project]
[0009] A polycrystalline cubic boron nitride (PcBN) composition is provided. The PcBN composition contains about 60% to about 80% by volume of a hard cBN phase based on the total volume of the PcBN composition. Furthermore, the composition has about 20% to about 40% by volume of a ceramic-bonding phase based on the total volume of the PcBN composition. The ceramic-bonding phase comprises an AlN phase, an Al2O3 phase, and at least one tough Co(x)W(y)B(z) phase.
[0010] Optionally, the ceramic bonding phase may include quasi-stoichiometric (ss) titanium nitride (TiN), titanium carbonitride (TiCN), or a combination thereof.
[0011] Optionally, the ceramic bonding phase may include quasi-stoichiometric or stoichiometric TiNO, TiCNO, or a combination thereof.
[0012] Optionally, the cBN particles have a particle size ranging from approximately 3 microns to approximately 6 microns.
[0013] Optionally, the cBN particles have a particle size in the range of approximately 2 microns to approximately 4 microns.
[0014] Optionally, the Co particles have a particle size ranging from approximately 0.1 microns to approximately 1 micron.
[0015] Optionally, tungsten carbide (WC) particles have a particle size ranging from approximately 0.1 microns to approximately 1 micron.
[0016] Optionally, (x) is 1, (y) is 2, (z) is 2, and at least one Co(x)W(y)B(z) tough phase contains CoW2B2.
[0017] Optionally, (x) is 1, (y) is 1, and (z) is 1, and at least one Co(x)W(y)B(z) tough phase contains CoWB.
[0018] Optionally, based on the total weight of the PcBN composition, the amount of aluminum is in the range of approximately 3% to 6% by weight, the amount of cobalt is in the range of approximately 0.9% to 2.5% by weight, and the amount of tungsten is in the range of approximately 5% to 8% by weight.
[0019] Furthermore, a method is provided for producing a sintered polycrystalline cubic boron nitride (PcBN) molded body, comprising: grinding a powder mixture containing powders that form a hard component of a ceramic binder phase, comprising (i) about 60% to about 80% by volume based on the total volume of the powder mixture and (ii) about 20% to about 40% by volume based on the total volume of the powder mixture, with a grinder containing at least tungsten carbide (WC) to form a powder blend and generate mill debris. Next, the formed powder mixture is dried. Finally, the components of the powder blend are reacted under high pressure and high temperature (HPHT) conditions to form an AlN phase, an Al2O3 phase, and at least one tough Co(x)W(y)B(z) phase in the ceramic binder phase.
[0020] Optionally, drying of the powder blend may include vacuum drying, air drying, freeze-drying, or spray drying.
[0021] Optionally, grinding may be carried out using one or more solvents as a grinding slurry of the powder blend, including ethanol, methanol, isopropanol, butanol, cyclohexanol, acetone, hexane, heptane, toluene, water, or any combination thereof.
[0022] Optionally, HPHT conditions include pressures ranging from approximately 4 gigapascals (GPa) to approximately 8 GPa and temperatures ranging from approximately 1100°C to approximately 1800°C.
[0023] Optionally, after drying the powder blend, place it into a heat-resistant metal cup.
[0024] Furthermore, cutting tools incorporating a PcBN composition are provided.
[0025] Furthermore, a molded article incorporating a PcBN composition is provided.
[0026] Other systems, methods, features, and advantages will be apparent to those skilled in the art upon consideration of the following figures and detailed description. All such additional systems, methods, features, and advantages are included herein, within the scope of this disclosure, and intended to be protected by the following claims. Nothing in this section should be construed as a limitation on these claims. Further embodiments and advantages are described below in relation to embodiments of this disclosure. It should be understood that both the above general description and the following detailed description of this disclosure are illustrative and descriptive, and are intended to provide further explanation of the disclosure as described in the claims.
[0027] The accompanying drawings, which are included to further deepen the understanding of the subject matter and are incorporated in and constitute a part of this specification, illustrate embodiments of the subject matter and serve to explain the principles of the present disclosure together with the specification. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] [Figure 1A] Fig. 2 depicts an exemplary shape of a support-free sintered polycrystalline cubic boron nitride (PcBN)-based compact incorporating cBN particles, according to exemplary embodiments of the present subject matter. [Figure 1B] Fig. 3 depicts an exemplary shape of a supported sintered polycrystalline cubic boron nitride (PcBN)-based compact incorporating cBN particles, according to exemplary embodiments of the present subject matter. [Figure 2] FIG. 4 is a flow diagram showing the individual process steps for manufacturing a sintered polycrystalline cubic boron nitride (PcBN)-based compact for use in a cutting tool, according to exemplary embodiments of the present subject matter. [Figure 3] FIG. 5 shows an X-ray diffraction (XRD) spectrum illustrating the phases present in an exemplary polycrystalline cubic boron nitride (PcBN)-based sintered body having a titanium nitride (TiN) ceramic binder. [Figure 4] FIG. 6 shows an X-ray diffraction (XRD) spectrum illustrating the phases present in an exemplary polycrystalline cubic boron nitride (PcBN)-based sintered body having a substoichiometric (ss) titanium carbonitride (TiCN) ceramic binder. [Figure 5A] FIG. 7 is a scanning electron microscope (SEM) image showing the microstructure of an exemplary polycrystalline cubic boron nitride (PcBN)-based sintered body having a titanium nitride (TiN) ceramic binder at a magnification of 2000×. [Figure 5B] FIG. 8 is a scanning electron microscope (SEM) image showing the microstructure of an exemplary polycrystalline cubic boron nitride (PcBN)-based sintered body having a titanium nitride (TiN) ceramic binder at a magnification of 10000×. [Figure 6A] FIG. 9 is a scanning electron microscope (SEM) image showing the microstructure of an exemplary polycrystalline cubic boron nitride (PcBN)-based sintered body having a substoichiometric (ss) titanium carbonitride (TiCN) ceramic binder at a magnification of 2000×. [Figure 6B] This is a scanning electron microscope (SEM) image at 10,000x magnification showing the microstructure of an exemplary polycrystalline cubic boron nitride (PcBN) sintered body with a quasi-stoichiometric (ss) titanium carbonitride (TiCN) ceramic binder. [Figure 7A] The X-ray diffraction (XRD) spectrum is shown for a phase present in formulation A (65 vol. cBN, 22 vol. to 23 vol. TiN, 5 wt% aluminum, 0.15 wt% cobalt, 2.6 wt% tungsten) of an exemplary polycrystalline cubic boron nitride (PcBN) sintered body having a titanium nitride (TiN) ceramic binder. [Figure 7B] The X-ray diffraction (XRD) spectrum is shown for a phase present in formulation B (65 vol. cBN, 21 vol. to 22 vol. TiN, 5 wt% aluminum, 1.4 wt% cobalt, 6.4 wt% tungsten) of an exemplary polycrystalline cubic boron nitride (PcBN) sintered body having a titanium nitride (TiN) ceramic binder. [Figure 7C] The X-ray diffraction (XRD) spectrum is shown for a phase present in formulation C (70 vol. cBN, 22 vol. to 23 vol. % TiN, 3.8 wt% aluminum, 0.2 wt% cobalt, 2.6 wt% tungsten) of an exemplary polycrystalline cubic boron nitride (PcBN) sintered body having a titanium nitride (TiN) ceramic binder. [Figure 7D] The X-ray diffraction (XRD) spectrum is shown for a phase present in formulation D (72 vol. cBN, 21 vol. to 22 vol. TiN, 4.1 wt% aluminum, 1.1 wt% cobalt, 5.2 wt% tungsten) of an exemplary polycrystalline cubic boron nitride (PcBN) sintered body having a titanium nitride (TiN) ceramic binder. [Figure 7E] The X-ray diffraction (XRD) spectrum is shown for a phase present in formulation E (62 vol. cBN, 22 vol. to 23 vol. TiN, 4.4 wt% aluminum, 0.2 wt% cobalt, 2.7 wt% tungsten) of an exemplary polycrystalline cubic boron nitride (PcBN) sintered body having a quasi-stoichiometric (ss) titanium carbonitride (TiCN) ceramic binder. [Figure 7F]The X-ray diffraction (XRD) spectrum is shown for a phase present in formulation F (70 vol. cBN, 21 vol. to 22 vol. tungsten) of an exemplary polycrystalline cubic boron nitride (PcBN) sintered body having a quasi-stoichiometric (ss) titanium carbonitride (TiCN) ceramic binder. [Modes for carrying out the invention]
[0029] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as they would be generally understood by those skilled in the art to which the subject matter described relates.
[0030] Where a range of values is provided, for example, a concentration range, a percentage range, or a ratio range, unless otherwise explicitly indicated in the context, each intervening value between the upper and lower limits of that range, up to one-tenth of the lower limit unit, and any other stated or intervening values within the stated range, are understood to be included within the described subject. The upper and lower limits of these narrower ranges may be independently included within the narrower range, and such embodiments are also included within the described subject, but may be modified to any specifically excluded limits within the stated range. If the stated range includes one or both limits, the range excluding one or both of those included limits is also included within the described subject.
[0031] The following definitions specify the parameters of the subject being described.
[0032] As used in this disclosure, the term “mill debris” generally refers to at least WC material formed from the grinding medium or mill lining due to friction between cBN abrasive particles, grinding material, and grinding lining. There are many factors that determine the amount of mill debris that may be generated, including, for example, at least the volume and density of the grinding medium, the size of the jar, and the viscosity of the grinding slurry. Mill debris usually increases in proportion to the grinding time, cBN particle size, and mill grinding speed. If cBN particles are present in the mill, a considerable amount of mill debris can naturally be generated because cBN particles are considerably harder and more rigid than cemented WC particles. Since WC particles are added to the blend for further processing by scraping, grinding, or abrading them from the cemented WC grinding medium, one method for measuring the particle size of WC obtained from mill debris is to employ scanning electron microscope (SEM) imaging. This is done by measuring a size called the ferret diameter. Those skilled in the art will know that in order to determine the ferret diameter, a rectangle completely surrounding the WC particles is first drawn. The length of the longer side of the rectangle represents the maximum ferret diameter. The length of the shorter side of the rectangle represents the minimum ferret diameter. In this way, by calculating the average maximum and average minimum ferret diameters of WC particles obtained from the mill debris from multiple SEM images, the particle size of the WC particles obtained from the mill debris can be finally determined.
[0033] As used in this disclosure, the term "PcBN molded body" refers to a sintered product consisting of a mass formed by the compression and bonding of multiple wear-resistant superabrasive cBN particles in any of the following ways: self-bonding, bonding by a bonding medium, or a combination thereof. As used in this disclosure, the term "PcBN composite molded body" refers to a PcBN molded body supported on a cemented WC substrate.
[0034] As used in the specification of this disclosure, the term “particle” refers to a separate object or a group of separate objects. As used in the specification of this disclosure, the term “particle” is also considered to be a crystal or a grain.
[0035] Where used in the specification of this disclosure, the terms “volume %” or “weight %” refer to a given volume percentage or weight percentage of (I) the total volume or total weight of the PcBN composition, (II) the total volume of the powder mixture, or (III) the total weight of the PcBN molded article, unless otherwise specified. Where “volume %” or “weight %” is referred to in this disclosure or the appended claims, it is also explicitly stated which volume percentage of (I), (II), or (III) it refers to in each of the given specific scenarios.
[0036] Grades can be classified, for example, according to particle size. Different types of grades of different types of materials are defined as nano, ultrafine, submicron, fine, medium-fine, medium-coarse, coarse, and ultra-coarse. As used in this disclosure, the terms (I) “nanograde” is defined as a component of a CBN composition having a particle size of less than about 0.2 microns; (II) “ultrafine grade” is defined as a component of a CBN composition having a particle size of about 0.2 microns to about 0.5 microns; (III) “submicron grade” is defined as a component of a CBN composition having a particle size of about 0.5 microns to about 0.9 microns; and (IV) “fine grade” is defined as a CBN composition having a particle size of about 1.0 micron to about 1.3 microns. (V) "Medium Grade" is defined as a component of a CBN composition having a particle size of approximately 1.4 microns to approximately 2.0 microns, (VI) "Medium-Coarse Grade" is defined as a component of a CBN composition having a particle size of approximately 2.1 microns to approximately 3.4 microns, (VII) "Coarse Grade" is defined as a component of a CBN composition having a particle size of approximately 3.5 microns to approximately 5.0 microns, and (VIII) "Very Coarse Grade" is defined as a component of a CBN composition having a particle size greater than approximately 5.0 microns.
[0037] As used in the specification of this disclosure, the terms “super-abrasive superhard material” or simply “super-abrasive material” refer to an abrasive material that exhibits superior hardness and wear resistance and can exhibit a Knoop indentation hardness greater than 2000, and are found in, but are not limited to, crystalline diamond, polycrystalline diamond (PCD), thermally stable polycrystalline diamond, chemically vapor-deposited (CVD) diamond, metal matrix diamond composites, ceramic matrix diamond composites, nanodiamonds, cubic boron nitride (cBN), polycrystalline cubic boron nitride (PcBN), or any combination thereof. As used herein, the term “abrasive” refers to any material used to abrade a softer material.
[0038] Where used in the specification of this disclosure, the term “about” means plus or minus 5% of the numerical values used in the claims and in this disclosure. Thus, “about” can be used to allow flexibility in the endpoint of a numerical range, and a given value may be “above” or “below” that given value. Therefore, for example, the value 50% is, for example, 47.5%~52.25%, 47.5%~52.5%, 47.75%~50%, 50%~52.5%, 48%~48.5%, 48%~48.75%, 48%~49%, 48%~49.5%, 48%~49.75%, 48%~50%, 48%~50.25%, 48%~50.5%, 48%~50.75%, 48%~51%, 48%~51.5%, 48%~51.75%, 48%~52%, 48%~52.25%, 48%~52.5% ,48.25%~48.5%,48.25%~48.75%,48.25%~49%,48.25%~49.5%,48.25%~49.75%,48.25%~50%,48.25%~50.25%,48.25%~50.5%,48.25%~50.75%,48.25%~51%,48.25%~51.25%,48.25%~51.5%,48.25%~51.75%,48.25%~52%,48.25%~52.25%,48.25%~52.5%,48.5%~48 0.75%, 48.5%~49%, 48.5%~49.5%, 48.5%~49.75%, 48.5%~50%, 48.5%~50.25%, 48.5%~50.5%, 48.5%~50.75%, 48.5%~51%, 48.5%~51.25%, 48.5%~51.5%, 48.5%~51.75%, 48.5%~52%, 48.5%~52.25%, 48.5%~52.5%, 49%~49.25%, 49%~49.5%, 49%~49.75%, 49%~50%, 49%~5 0.25%, 49%~50.5%, 49%~50.75%, 49%~51%, 49%~51.25%, 49%~51.5%, 49%~51.75%, 49%~52%, 49%~52.25%, 49%~52.5%, 49.5%~49.75%, 49.5%~50%, 49.5%~50.25%, 49.5%~50.5%, 49.5%~50.75%, 49.5%~51%, 49.5%~51.5%, 49.5%~51.75%, 49.5%~52%, 49.5%~52.25%, 49.It may be intended to include ranges that can be defined by ranges such as 5%~52.5%, 49.75%~50%, 49.75%~50.25%, 49.75%~50.5%, 49.75%~50.75%, 49.75%~51%, 49.75%~51.25%, 49.75%~51.5%, 49.75%~51.75%, 49.75%~52%, 49.75%~52.25%, 49.75%~52.5%, 50%~50.25%, 50%~50.5%, 50%~50.75%, 50%~51%, 50%~51.25%, 50%~51.5%, 50%~52%, 50%~52.25%, 50%~52.5%, etc.
[0039] When used throughout this disclosure, the term “generally” means “usually,” “in close proximity,” or “in the vicinity or within the scope of.”
[0040] As used herein, the term “substantially” refers to the complete or nearly complete range or extent of an action, characteristic, nature, state, structure, item, or result.
[0041] As used herein, “spherical” refers to particles having a substantially “round” shape.
[0042] As used in the specification of this disclosure, the term “fracture toughness” refers to the ability of a material to withstand fracturing and / or crack propagation.
[0043] As used in this disclosure, the term “high-pressure, high-temperature (HPHT) sintering” typically refers to a process of heating under pressures ranging from about 4 gigapascals (GPa) to about 8 GPa to minimize the surface area of a cBN-based particle system, a process associated with the formation of bonds between adjacent small cBN particles or cBN granules and the subsequent contraction of the aggregated cBN particles or cBN granules. Heating small cBN particles under pressure results in the compression formation of a high-density bulk mass. Atoms in the small cBN particles diffuse across the boundaries of the cBN particles, fusing the small cBN particles together, thereby forming a single, solid, high-density bulk piece.
[0044] Polycrystalline cubic boron nitride (PcBN) composition This disclosure presents a polycrystalline cubic boron nitride (PcBN) composition in which the hard cBN phase reacts with high levels of metal content aluminum (Al), cobalt (Co), and tungsten (W) present in the ceramic binder phase. The ceramic binder consists of quasi-stoichiometric (ss) titanium nitride (TiN), titanium carbonitride (TiCN), or a combination thereof, i.e., the ratio N / Ti or CN / Ti is substantially less than 1. The ceramic binder in the PcBN composition exhibits improved fracture toughness through the reaction of Co in the ceramic binder with additional mill debris containing at least tungsten carbide (WC) particles. While we do not wish to be bound by theory, it has been assumed that unreacted WC particles (i.e., mill debris) generated during grinding function as crack propagation pathways. The reader will understand that there are at least many advantages to simply adding WC-containing powder. The first issue is that the mill debris is uniformly dispersed throughout the blend to which it is added. Secondly, mill debris is extremely fine, typically less than about 1 micron. In fact, sourcing, safely handling, and dispersing submicron powder is a fairly difficult task in this matter, and therefore, the current subject will avoid such challenges. During high-pressure, high-temperature (HPHT) sintering, the Co in the ceramic binder reacts with the WC particles obtained from the mill debris and the boron in the cBN, as described in paragraph ¶
[0046] , thereby forming at least one distinct tough Co(x)W(y)B(z) phase in the ceramic binder, where the cobalt no longer functions as a binder but instead functions as a hard phase. In other words, the cobalt in at least one tough Co(x)W(y)B(z) phase is no longer metallic. In one example, (x) is 1, (y) is 2, (z) is 2, and at least one Co(x)W(y)B(z) tough phase contains CoW2B2. In another example, (x) is 1, (y) is 1, and (z) is 1, and at least one Co(x)W(y)B(z) tough phase contains CoWB. The individual phases further formed in the ceramic binder are at least an AlN phase and an Al2O3 phase. The pulverized material consists of 94 wt% WC and 6 wt% Co.The mill debris has the same composition as the pulverized material, namely 94 wt% WC and 6 wt% Co. However, a cobalt content of 6 wt% is generally insufficient to form the tough CoW2B2 phase described above. Therefore, additional metallic cobalt is usually added to the pulverized slurry. The carbon removed from the WC is instead integrated into the TiN / TiCN matrix of the ceramic binder.
[0045] The cBN hard phase can typically be present in about 60% to about 80% of the total volume of the PcBN composition. In some examples, the cBN hard phase is present in about 62% to about 80% of the total volume of the PcBN composition. In other examples, the cBN hard phase is present in about 65% to about 80% of the total volume of the PcBN composition. In yet another example, the cBN hard phase is present in about 67% to about 80% of the total volume of the PcBN composition. In yet another example, the cBN hard phase is present in about 69% to about 80% of the total volume of the PcBN composition. In yet another example, the cBN hard phase is present in about 71% to about 80% of the total volume of the PcBN composition. In yet another example, the cBN hard phase is present in about 73% to about 80% of the total volume of the PcBN composition. In other embodiments, the cBN hard phase is present in about 75% to about 80% by volume based on the total volume of the PcBN composition. In yet another embodiment, the cBN hard phase is present in about 77% to about 80% by volume based on the total volume of the PcBN composition. Even in yet another embodiment, the cBN hard phase is present in about 78% to about 80% by volume based on the total volume of the PcBN composition.
[0046] The cBN hard phase is also divided into approximately 60% by volume to approximately 62% by volume, 60% by volume to approximately 65% by volume, approximately 62% by volume to approximately 65% by volume, approximately 65% by volume to approximately 67% by volume, approximately 60% by volume to approximately 67% by weight, approximately 60% by volume to approximately 70% by weight, approximately 60% by volume to approximately 72% by weight, approximately 60% by volume to approximately 75% by weight, approximately 67% by volume to approximately 69% by volume, and approximately 69% by weight. It may exist in the following proportions: approximately 71% to 73% by volume, approximately 67% to 73% by volume, approximately 67% to 75% by volume, approximately 67% to 77% by volume, approximately 70% to 75% by volume, approximately 70% to 77% by volume, approximately 70% to 79% by volume, approximately 73% to 75% by volume, approximately 73% to 77% by volume, or approximately 75% to 77% by volume.
[0047] The ceramic binders described in this disclosure may generally consist of carbides, borides, nitrides, carbonitrides, or oxides of at least one metal selected from Groups 4, 5, and 6 of the periodic table, or any combination thereof.
[0048] In certain embodiments, the ceramic binder consists of quasi-stoichiometric (ss)TiN, TiCN, or a combination thereof. While we do not wish to be bound by any particular theory, Ti-containing binders (e.g., TiN, TiCN) can function as ceramic binders and are generally considered to have a similar effect in improving the cutting ability of tools formed by molded bodies. In yet other embodiments, the ceramic binder consists of quasi-stoichiometric or stoichiometric TiNO, TiCNO, or a combination thereof.
[0049] Ceramic binders and grain growth inhibitors during sintering, such as vanadium carbide (VC), chromium carbide (Cr3C2), tantalum carbide (TaC), titanium carbide (TiC), zirconium carbide (ZrC), and niobium carbide (NbC), may be present in the PcBN composition in any possible combination that is compatible and does not contradict the objectives of this subject.
[0050] The ceramic binder phase can typically be present in about 20% to about 40% by volume based on the total volume of the PcBN composition. In some examples, the ceramic binder phase is present in about 22% to about 40% by volume based on the total volume of the PcBN composition. In other examples, the ceramic binder phase is present in about 24% to about 40% by volume based on the total volume of the PcBN composition. In yet another example, the ceramic binder phase is present in about 26% to about 40% by volume based on the total volume of the PcBN composition. In yet another example, the ceramic binder phase is present in about 28% to about 40% by volume based on the total volume of the PcBN composition. In yet another example, the ceramic binder phase is present in about 30% to about 40% by volume based on the total volume of the PcBN composition. In yet another example, the ceramic binder phase is present in about 32% to about 40% by volume based on the total volume of the PcBN composition. In other embodiments, the ceramic binder phase is present in about 34% to about 40% by volume based on the total volume of the PcBN composition. In yet another embodiment, the ceramic bonding phase is present in an amount of about 36% to about 40% by volume based on the total volume of the PcBN composition. In yet another embodiment, the ceramic bonding phase is present in an amount of about 38% to about 40% by volume based on the total volume of the PcBN composition.
[0051] The ceramic bonding phase is also based on the total volume of the PcBN composition, with approximately 20% to 22% by volume, approximately 22% to 24% by volume, approximately 24% to 26% by volume, approximately 26% to 28% by volume, approximately 20% to 25% by volume, approximately 20% to 26% by volume, approximately 20% to 27% by volume, approximately 20% to 28% by volume, approximately 20% to 29% by volume, approximately 20% to 30% by volume, approximately 25% to 30% by volume, and 26% by volume. It may exist in the following proportions: approximately 30% by volume, approximately 27% by volume, approximately 30% by volume, approximately 28% by volume, approximately 30% by volume, approximately 29% by volume, approximately 30% by volume, approximately 32% by volume, approximately 30% by volume, approximately 35% by volume, approximately 30% by volume, approximately 37% by volume, approximately 32% by volume, approximately 34% by volume, approximately 32% by volume, approximately 35% by volume, approximately 34% by volume, approximately 36% by volume, approximately 38% by volume, approximately 35% by volume, approximately 40% by volume, or approximately 38% by volume.
[0052] Grain growth inhibitors are typically based on the total volume of the PcBN composition, ranging from approximately 1% to 2% by volume, 1% to 3% by volume, 2% to 5% by volume, 5% to 7% by volume, 3% to 7% by volume, 7% to 10% by volume, 10.1% by volume, 10.2% by volume, 10.3% by volume, 10.4% by volume, 10.5% by volume, 10.6% by volume, 10.7% by volume, 10.8% by volume, 10.9% by volume, and 7% to 20% by volume. It may exist in the following proportions: by volume%, approximately 10% to 20% by volume%, approximately 12% to 20% by volume%, approximately 15% to 20% by volume%, approximately 17% to 20% by volume%, approximately 10% to 12% by volume%, approximately 10% to 15% by volume%, approximately 10% to 17% by volume%, approximately 10% to 20% by volume%, approximately 15% to 20% by volume%, or approximately 17% to 20% by volume.
[0053] cBN particles can typically have a particle size in the range of about 2 to 4 microns, or about 3 to 6 microns. In some examples, cBN particles have a particle size of about 2.5 to 4 microns. In other examples, cBN particles have a particle size of about 3 to 4 microns. In yet another example, cBN particles have a particle size of about 3.5 to 4 microns. In yet another example, cBN particles have a particle size of about 3.5 to 6 microns. In yet another example, cBN particles have a particle size of about 4 to 6 microns. Even yet another example, cBN particles have a particle size of about 4.5 to 6 microns. Even yet another example, cBN particles have a particle size of about 5 to 6 microns. In other embodiments, cBN particles have a particle size of about 5.5 to 6 microns.
[0054] cBN particles are also found in the following sizes: approximately 2 microns to 2.25 microns, approximately 2 microns to 2.5 microns, approximately 2 microns to 2.75 microns, approximately 2 microns to 3 microns, approximately 2 microns to 3.25 microns, approximately 2 microns to 3.5 microns, approximately 2 microns to 3.75 microns, approximately 2.5 microns to 2.75 microns, approximately 2.5 microns to 3 microns, approximately 2.5 microns to 3.25 microns, 2.5 microns to 3.5 microns, approximately 2.5 microns to 3.75 microns, approximately 2.25 microns to 2.5 microns, and approximately 2.25 microns to 2. 75 microns, approximately 2.25 microns to approximately 3 microns, approximately 2.25 microns to approximately 3.25 microns, approximately 2.25 microns to approximately 3.5 microns, approximately 2.25 microns to approximately 3.75 microns, approximately 2.25 microns to approximately 4 microns, approximately 2.5 microns to approximately 3.25 microns, approximately 2.75 microns to approximately 3.25 microns, approximately 2.75 microns to approximately 3.5 microns, approximately 3 microns to approximately 3.25 microns, approximately 3 microns to approximately 3.5 microns, approximately 2.75 microns to approximately 3.75 microns, approximately 3 microns to approximately 3.5 microns, approximately 3 microns to approximately 3.75 microns, approximately 2. 5 microns to approximately 4 microns, approximately 2.75 microns to approximately 4 microns, approximately 3.25 microns to approximately 4 microns, approximately 3.5 microns to approximately 4 microns, approximately 3.75 microns to approximately 4 microns, approximately 3 microns to approximately 4.25 microns, approximately 3 microns to approximately 4.5 microns, approximately 3 microns to approximately 4.75 microns, approximately 3 microns to approximately 5 microns, approximately 3 microns to approximately 5.25 microns, approximately 3 microns to approximately 5.5 microns, approximately 3 microns to approximately 5.75 microns, approximately 4 microns to approximately 4.25 microns, approximately 4 microns to approximately 4.5 microns, approximately 4 microns to approximately 4.75 microns, approximately 4 microns Chron ~ approximately 5 microns, approximately 4 microns ~ approximately 5.25 microns, approximately 4 microns ~ approximately 5.5 microns, approximately 4 microns ~ approximately 5.75 microns, approximately 4.5 microns ~ approximately 4.75 microns, approximately 4.5 microns ~ approximately 5 microns, approximately 4.5 microns ~ approximately 5.25 microns, approximately 4.5 microns ~ approximately 5.5 microns, approximately 4.5 microns ~ approximately 5.75 microns, approximately 4.5 microns ~ approximately 6 microns, approximately 4.75 microns ~ approximately 5 microns, approximately 4.75 microns ~ approximately 5.25 microns, approximately 4.75 microns ~ approximately 5.5 microns, approximately 4.75 microns ~ approximately 5.75 microns, approximately 4.The particle size may range from 75 microns to approximately 6 microns, approximately 5 microns to approximately 5.25 microns, approximately 5.25 microns to approximately 5.5 microns, approximately 5 microns to approximately 5.5 microns, or approximately 5 microns to approximately 5.75 microns.
[0055] WC particles in mill debris can typically have particle sizes ranging from about 0.1 microns to about 1 micron. In certain embodiments, WC particles may range from about 0.1 to about 0.2 microns, about 0.2 to about 0.3 microns, about 0.3 to about 0.4 microns, about 0.1 to about 0.4 microns, 0.1 to about 0.5 microns, 0.2 to about 0.5 microns, 0.3 to about 0.5 microns, about 0.4 to about 0.5 microns, about 0.5 to about 0.6 microns, about 0.5 to about 0.7 microns, about 0.5 to about 0.8 microns, about 0.5 to about 0.9 microns, about 0.5 to about 1.0 microns, and about 0.6 to about 0.7 microns. The particles have a particle size of approximately 0.4 to 0.7 microns, approximately 0.4 to 0.8 microns, approximately 0.4 to 0.9 microns, approximately 0.4 to 1.0 microns, approximately 0.7 to 0.8 microns, approximately 0.8 to 0.9 microns, approximately 0.1 to 1.0 microns, approximately 0.2 to 1.0 microns, approximately 0.3 to 1.0 microns, approximately 0.4 to 1.0 microns, approximately 0.6 to 1.0 microns, approximately 0.7 to 1.0 microns, approximately 0.8 to 1.0 microns, or approximately 0.9 to 1.0 microns.
[0056] Co particles can typically have particle sizes ranging from about 0.1 microns to about 1 micron. In certain embodiments, the Co particles may range from about 0.1 to about 0.2 microns, about 0.2 to about 0.3 microns, about 0.3 to about 0.4 microns, about 0.1 to about 0.4 microns, about 0.1 to about 0.5 microns, about 0.2 to about 0.5 microns, about 0.3 to about 0.5 microns, about 0.4 to about 0.5 microns, about 0.5 to about 0.6 microns, about 0.5 to about 0.7 microns, about 0.5 to about 0.8 microns, about 0.5 to about 0.9 microns, about 0.5 to about 1.0 microns, and about 0.6 to about 0. They have particle sizes of 0.7 microns, approximately 0.4 to 0.7 microns, approximately 0.4 to 0.8 microns, approximately 0.4 to 0.9 microns, approximately 0.4 to 1.0 microns, approximately 0.7 to 0.8 microns, approximately 0.8 to 0.9 microns, approximately 0.1 to 1.0 microns, approximately 0.2 to 1.0 microns, approximately 0.3 to 1.0 microns, approximately 0.4 to 1.0 microns, approximately 0.6 to 1.0 microns, approximately 0.7 to 1.0 microns, approximately 0.8 to 1.0 microns, or approximately 0.9 to 1.0 microns.
[0057] To determine a specific cBN particle size or a specific Co particle size, a person skilled in the art can typically employ one of the following: dynamic digital image analysis (DIA), static laser scattering (SLS), also known as laser diffraction, or visual measurement using an electron microscope, a technique known as image analysis and optical obscuration. Each method covers a characteristic size range that can be measured. These ranges partially overlap. However, even measurements of the same sample can all be different, depending on the specific method used. A person skilled in the art who wishes to determine particle size or particle size distribution will readily know whether each of the methods mentioned is commonly performed and practiced. Therefore, for further insight into each procedure and methodology, the reader should refer, for example, to (i) "Dynamic Digital Image Analysis, Laser Diffraction, and Sieve Analysis," Lechts Technologies, and (ii) the scientific publication "Graphic Comparison of Image Analysis Data and Laser Diffraction Particle Size Distribution Data Obtained from Measurements of Non-Spherical Particle Systems," by Kelly et al., AAPS PharmSciTech., August 18, 2006, Vol. 7(3), Article No. 69. Furthermore, all of these references are incorporated herein by reference in their entirety.
[0058] A molded body ideally containing a cemented WC substrate with a support is known in the metallurgical field as a supported molded body. Alternatively, the manufacturing process can be carried out without the presence of a cemented WC substrate with a support, in which case the recovered molded body is known in the metallurgical field as an unsupported molded body. Figures 1A and 1B show exemplary shapes of an unsupported molded body 10 and a supported molded body 20, respectively. The supported molded body 20 shown in Figure 1B typically comprises a body 30 made of sintered cBN particles, which is supported on a cemented WC substrate 35 and further fixed within a matrix of ceramic binder material bonded via a transition interface. Optionally, these can be manufactured as freestanding / unsupported PCBN materials. The Co in the ceramic binder reacts with the WC present in the added mill debris, which contains at least WC, and the boron in the body 30, thus forming at least one distinct tough Co(x)W(y)B(z) phase during the HPHT sintering solidification operation as further described in paragraphs ¶
[0079] to
[0080] . In one example, (x) is 1, (y) is 2, (z) is 2, and at least one tough Co(x)W(y)B(z) phase contains CoW2B2. In another example, (x) is 1, (y) is 1, (z) is 1, and at least one tough Co(x)W(y)B(z) phase contains CoWB. The individual phases further formed in the ceramic binder are at least an AlN phase and an Al2O3 phase. Based on the total weight of the PcBN molded body, the amount of aluminum may range from approximately 3% to 6% by weight, the amount of cobalt may range from approximately 0.9% to 2.5% by weight, and the amount of tungsten may range from approximately 5% to 8% by weight. Similarly, the unsupported molded body 10 shown in Figure 1A also includes a body 15 containing sintered cBN particles. In both the unsupported molded body 10 shown in Figure 1A and the supported molded body 20 shown in Figure 1B, the sintered bodies 15 and 30 consist of a plurality of compressed and bonded wear-resistant cBN particles. Each of the plurality of cBN particles contains a plurality of subparticles.Each subparticle, when typically measured using a Microtrac particle characterization system, may generally exhibit a size ranging from less than 1 micron to approximately 2 microns, or alternatively, from approximately 0.1 microns to approximately 1.5 microns. A typical, exemplary separate cBN particle with a particle size of approximately 1 to 2 microns may contain, for example, approximately 10 to 5000 subparticles.
[0059] Method for manufacturing sintered polycrystalline cubic boron nitride (PcBN) molded bodies Now, focusing on Figure 2, this figure shows a flowchart 200 illustrating each process step for manufacturing a PcBN molded body for use in a tool, according to an exemplary embodiment of the subject.
[0060] In step 202, an exemplary step 200 includes, for example, mixing powders that form (i) about 60% to about 80% by volume of a cBN hard phase based on the total volume of the powder mixture and (ii) about 20% to about 40% by volume of a hard component of a ceramic binding phase based on the total volume of the formed powder mixture, wherein the pulverized body contains at least tungsten carbide (WC).
[0061] In step 204, the desired particle size of the cBN powder and ceramic binder powder can be produced by grinding the powder mixture together with the metal binder in the ceramic binder for several hours (e.g., 8, 16, 32, 64 hours) under typical ambient conditions (i.e., 25°C, 298.15K, and a pressure of 101.325kPa in a ball mill, attritor mill, or planetary mill) to form a powder blend and generate mill debris containing at least WC. The general purpose of mixing by grinding is to promote a good distribution of the ceramic binder and good wettability between the cBN components and the ceramic binder powder mixture, thereby forming a powder blend. In some cases, the cBN powder and ceramic binder powder may be crushed or otherwise finely ground before grinding together with the metal binder.
[0062] As will be apparent to those skilled in the art, the grinding in step 204 is carried out by first adding the grinding liquid to the cBN and ceramic binder powder to form a grinding slurry. The grinding liquid may be water, alcohol such as ethanol, methanol, isopropanol, butanol, cyclohexanol, organic solvent such as hexane, heptane, acetone, toluene, or water, an alcohol mixture, an alcohol and solvent mixture, or any combination thereof.
[0063] Step 200 may include a drying operation in step 206. The pulverized powder blend may be dried using any conventional technique such as vacuum drying, air drying, freeze-drying, or spray drying to substantially remove the solvent in the pulverized slurry, for example, by evaporating it.
[0064] Step 200 may also optionally include, in step 208, placing the dry powder blend into a heat-resistant metal cup.
[0065] Next, step 200 may include an HPHT sintering solidification operation in step 210. A heat-resistant metal cup containing a dry powder blend can be placed in an HPHT cell, and HPHT sintering conditions can be applied to form a sintered PcBN molded body for use in the tools disclosed herein. Step 210 is performed at a pressure ranging from approximately 4 gigapascals (GPa) to approximately 8 GPa, approximately 5 GPa to approximately 8 GPa, approximately 6 GPa to approximately 8 GPa, approximately 7 GPa to approximately 8 GPa, approximately 5 GPa to approximately 6 GPa, approximately 5 GPa to approximately 7 GPa, or approximately 6 GPa to approximately 7 GPa, and at temperatures ranging from approximately 1100°C to approximately 1500°C, approximately 1100°C to approximately 1600°C, approximately 1100°C to approximately 1700°C, approximately 1100°C to approximately 1800°C, approximately 1200°C to approximately 1500°C, approximately 1200°C to approximately 1600°C, and approximately 1200°C to approximately 1700°C. This may include sintering at temperatures in the range of 1200°C to 1800°C, 1300°C to 1400°C, 1300°C to 1500°C, 1300°C to 1600°C, 1300°C to 1700°C, 1300°C to 1800°C, 1400°C to 1500°C, 1400°C to 1600°C, 1500°C to 1600°C, 1500°C to 1700°C, 1500°C to 1800°C, 1600°C to 1800°C, or 1700°C to 1800°C.
[0066] A specific range of sintering pressure and sintering temperature is selected so that the ceramic binder phase is sufficiently melted. The sintered PcBN molded body may contain cBN particles uniformly or substantially uniformly dispersed in the ceramic binder phase. During the HPHT sintering solidification process, the Co in the ceramic binder reacts with the WC particles obtained from the mill debris and the boron in the body 30 as described above in paragraph ¶
[0046] , thereby forming at least one individual tough Co(x)W(y)B(z) phase. In one example, (x) is 1, (y) is 2, (z) is 2, and at least one Co(x)W(y)B(z) tough phase contains CoW2B2. In another example, (x) is 1, (y) is 1, (z) is 1, and at least one Co(x)W(y)B(z) tough phase contains CoWB. Individual phases further formed in the ceramic binder are at least an AlN phase and an Al2O3 phase.
[0067] Those skilled in the art will readily understand how HPHT sintering solidification procedures for forming cBN are generally carried out. Therefore, readers should refer to, for example, U.S. Patent No. 5,512,235, U.S. Patent No. 10,196,314, and U.S. Patent No. 10,252,947 for further insight into various HPHT sintering procedures, techniques, and methodologies. All of these documents are incorporated herein by reference in their entirety.
[0068] In step 210, after the HPHT sintering solidification operation is completed, the resulting PcBN molded body can be machined to form a PcBN molded disc. The machining may be carried out through processes commonly known in the art to form a suitable cutting tool. Here, the machining may appropriately include electrical discharge machining (EDM), electrical discharge grinding (EDG), or other processes to form the PcBN molded body into a desired shape. A suitable shape may include, for example, an 80° to 120° triangle, thereby effectively forming a tip that can be used for various cutting and machining applications after the disc is brazed to the carbide tool body.
[0069] Molded bodies formed using the PcBN compositions described herein can be advantageously used in the manufacture of cutting tools. In some embodiments, PcBN molded bodies manufactured using the PcBN compositions can be used to form cutting insert blanks for general machining of metals and metal alloys. Thus, PcBN molded bodies formed according to step 200 can be used, for example, for machining hard-to-machine metals or metal alloys. For example, in such a scenario, PcBN molded bodies formed according to step 200 can be formed into cutting tools for machining high-strength alloys. In other embodiments, PcBN molded bodies can be used to manufacture intermittent cutting tools, such as vane end mills and / or milling inserts.
[0070] In summary, PcBN molded articles formed using the PcBN compositions of this specification can provide improved abrasion resistance and excellent wear resistance, thereby significantly improving cutting and machining properties, and ultimately resulting in a valuable extension of the lifespan of the cutting tools thus manufactured. [Examples]
[0071] The following examples are provided to give a complete disclosure and explanation of the manufacturing method and use of the subject matter described, and are not intended to limit the scope of what the inventors consider to be such disclosure, nor are they intended to represent all or only experiments that have been performed. While efforts have been made to ensure accuracy with respect to the numerical values used, some experimental error and deviation should be taken into consideration.
[0072] Example 1 Phase identification using X-ray diffraction (XRD) spectra and scanning electron microscopy (SEM), and image analysis of sintered polycrystalline cubic boron nitride (PcBN) compressed materials.
[0073] X-ray diffraction (XRD) spectra were performed on the sintered PcBN molded materials disclosed herein to identify the different phases present in the PcBN molded material. Figures 3 and 4 show exemplary XRD spectra when either (i) a TiN ceramic binder (exemplary molded material 1) or (ii) a quasi-stoichiometric (ss)TiCN ceramic binder (exemplary molded material 2) was used, respectively. These materials were produced by standard methodological procedures for manufacturing PcBN molded bodies. The TiN and ss TiCN ceramic binder materials and cBN were mixed in ethanol to first form a pulverized slurry, which was then typically pulverized in an attritor mill for at least 8 hours to ensure a uniform distribution of cBN and to generate the desired level of cemented WC / Co mill debris. In the final PcBN molded body, a sufficient amount of cobalt was added to ensure the formation of the desired Co(x)W(y)B(z) phase. Subsequently, the obtained pulverized slurry was dried by vacuum drying, air drying, freeze drying, or spray drying. The dried PcBN material supported on the resulting cemented carbide substrate was further processed by subjecting the PcBN material to an HPHT operation by applying the high-pressure, high-temperature (HPHT) reaction parameters described in paragraph ¶
[0079] . The resulting sintered PcBN molded body was ground to size, cut into appropriate shapes such as 80° to 120° triangles, brazed to a cemented carbide tool body, and finally formed into a cutting tool.
[0074] From the XRD spectra in Figures 3 and 4, it was confirmed that exemplary molded material 1 and exemplary molded material 2 contain cBN, TiN, or ssTiCN ceramic bonded phases. The Co(x)W(y)B(z) phase is identified as existing as crystalline CoW2B2. As seen in Figures 3 and 4, the cBN phase is identified as a peak appearing at approximately 7000 intensity counts on the y axis and approximately 43° on the x axis (00-035-1365 in Figure 3 and 00-025-1033 in Figure 4). In Figure 3, the TiN phase is represented by peaks appearing at approximately 1000, 2500, 4500 and 6000 intensity counts on the y axis and approximately 36°, 42°, 62°, 73° and 77° on the x axis (00-038-1420 in Figure 3). In Figure 4, ssTiC 0.7 N 0.3 The phase is represented by peaks identified at approximately 1000, 2000, 3000, 6000, and 6800 intensity counts on the y-axis, and approximately 36°, 42°, 62°, 73°, and 77° on the x-axis (00-042-1489 in Figure 4). The CoW2B2 phase is observed to have multiple peaks in Figures 3 and 4 (04-004-0327 in Figure 3 and 00-025-1082 in Figure 4). Finally, further phases identified by XRD spectral analysis include at least titanium boride (TiB2 in Figure 3, 00-008-0121 and 00-008-0121 in Figure 4), aluminum nitride (AlN, 04-006-2061 in Figure 3 and 00-025-1133 in Figure 4), and aluminum oxide (Al2O3, 00-005-0712 in Figure 3 and 00-010-0173 in Figure 4).
[0075] Scanning electron microscope (SEM) images of sintered PcBN-based molded bodies disclosed herein were also prepared to identify the components of the molded bodies. Figures 5A and 5B are scanning electron microscope (SEM) images of the microstructure of exemplary PcBN-based sintered molded bodies containing titanium nitride (TiN) ceramic binders, at magnifications of 2000x and 10000x, respectively. Similarly, Figures 6A and 6B are scanning electron microscope (SEM) images of the microstructure of exemplary PcBN-based sintered bodies equally containing ss titanium carbonitride (TiCN) ceramic binders, at magnifications of 2000x and 10000x, respectively. In the SEM images, cBN particles are identified as dark regions reflected by the digit 500 in Figures 5A and 5B and by the digit 600 in Figures 6A and 6B. Aluminum, being a relatively bright metal, is identified as a relatively dark gray region reflected by the digits 502 in Figures 5A and 5B and 602 in Figures 6A and 6B. The titanium-containing region is identified as a lighter gray region reflected by the digits 504 in Figures 5A and 5B and 604 in Figures 6A and 6B. Finally, both Co and W appear as bright white regions reflected by the digits 506A and 506 in Figures 5A and 5B, respectively, and by the digits 606A and 606 in Figures 6A and 6B, respectively.
[0076] Example 2 Machining of surface-treated 8620 steel (case-hardened 8620 steel) using sintered polycrystalline cubic boron nitride (PCBN) molded material.
[0077] A workpiece made of surface-treated 8620 steel is cut with a PcBN-based molded material manufactured as described above in paragraph ¶
[0087] , and (i) a conventional grade (*) comprising at least about 65 volume% based on the total volume of the PcBN composition, about 22 to 23 volume% based on the total volume of the PcBN composition, 5 wt% Al, 2.6 wt% W, and 0.15 wt% Co based on the total weight of the PcBN composition, and is subjected to energy-dispersive spectroscopy (EDS) analysis (with an XRD spectrum as shown in Figure 7A). The conventional grade (*) in Table 1, measured by formulation A) indicated by an asterisk (*), was compared with the present invention grade, which (ii) contains at least about 65 vol% based on the total volume of the PcBN composition, about 21 vol% to 22 vol% based on the total volume of the PcBN composition, 5 wt% Al, 6.4 wt% W, and 1.4 wt% Co based on the total weight of the PcBN composition, and was measured by EDS analysis (formulation B in Table 1, having the XRD spectrum shown in Figure 7B).
[0078] In Table 1, both the conventional grade (i) and the inventive grade (ii), indicated by an asterisk (*), showed cBN particle sizes in the range of approximately 2 microns to 4 microns. The feed rate for the surface-treated 8620 steel was 0.2 mm / revolution, the depth of cut for the surface-hardened 8620 steel was 0.15 mm, and the cutting speed for the surface-treated 8620 steel was 200 m / min. The results obtained were as follows: In the case of minor interruptions, the conventional grade failed due to fracture after an average cutting distance of 0.39 linear km. On the other hand, the inventive grade performed better, failing due to fracture after an average cutting distance of 0.44 linear km. In the case of serious interruptions, the conventional grade failed due to fracture after an average cutting distance of 0.34 linear km. In contrast, the inventive grade also performed better in this case, failing due to fracture after an average cutting distance of 0.41 linear km.
[0079] Additional formulations were tested, for example, conventional grade C (Formulation C) indicated by an asterisk (*) having a TiN binder with the XRD spectrum shown in Figure 7C, and conventional grade E (Formulation E) indicated by an asterisk (*) having a TiCN binder with the XRD spectrum shown in Figure 7E, were compared with the present invention grade D (Formulation D) and present invention grade F (Formulation F), respectively, having the XRD spectra shown in Figures 7D and 7F, as shown in Table 1.
[0080] As shown in Table 1, the trend observed was that, in general, the materials of the present invention showed longer tool life in severe interruption tests compared to each of the conventional compositions.
[0081] In conclusion, the data obtained demonstrates that the present invention grade is clearly superior to the conventional grade. TIFF0007940042000001.tif55170
[0082] While the present disclosure has been described in relation to its embodiments, it will be understood by those skilled in the art that additions, deletions, modifications, and substitutions not specifically described may be made without departing from the spirit and scope of the present disclosure as defined in the appended claims.
[0083] With regard to the use of substantially any plural and / or singular terms herein, those skilled in the art can convert from plural to singular and / or singular to plural as appropriate to the context and / or use. Various singular / plural permutations are not explicitly listed herein for clarity.
[0084] The subject matter described herein may also refer to different components that are contained within or connected to other different components. It should be understood that the architectures shown in this manner are merely illustrative, and in practice, many other architectures can be implemented to achieve the same functionality. Conceptually, any arrangement of components to achieve the same functionality is effectively “associated” in such a way that the desired functionality is achieved. Therefore, in this specification, any two components combined to achieve a particular functionality can be considered “associated” with each other, regardless of architecture or intermediate components, in such a way that the desired functionality is achieved. Similarly, any two such associated components can also be considered “operably connected” or “operably coupled” with each other to achieve the desired functionality, and any two components that can be associated in this way can also be considered “operably coupled” with each other to achieve the desired functionality. Specific examples of operably coupled components include, but are not limited to, physically matable and / or physically interacting components, and / or wirelessly interactable and / or wirelessly interacting components, and / or logically interacting and / or logically interactable components.
[0085] One or more components may be referred to herein as “configured to,” “configured by,” “configurable to,” “operable / operate to,” “adaptable / adaptable,” “adaptable / adaptable to.” Those skilled in the art will recognize that such terms (e.g., “configured to”) can generally encompass active components and / or inactive components and / or standby components, unless otherwise required by the context.
[0086] While specific aspects of the subject matter described herein have been shown and explained, changes and modifications can be made based on the teachings herein without departing from the subject matter described herein and its broader aspects, and it will be apparent to those skilled in the art that the appended claims encompass within their scope all such changes and modifications that are true in intent and within the scope of the subject matter described herein. In general, it will be understood to those skilled in the art that the terms used herein, and in particular in the appended claims (e.g., in the body of the appended claims), are generally intended to be “open” terms (for example, the term “includes” should be interpreted as “includes but not limited to,” the term “has” should be interpreted as “has at least,” and the term “includes” should be interpreted as “includes but not limited to.”).
[0087] Those skilled in the art will further understand that if a claim is intended to describe a specific number, such intent is explicitly stated in the claim, and if it is not, such intent does not exist. For example, to aid understanding, the following appended claims may include the use of the introductory phrases “at least one” and “one or more” to introduce the description of the claims. However, the use of such phrases should not be interpreted as meaning that the introduction of a claim description by the indefinite article “a” or “an” limits any particular claim containing such introduced description to a claim containing only one such description, even if the same claim contains the introductory phrase “one or more” or “at least one” and an indefinite article such as “a” or “an” (for example, “a” and / or “an” should usually be interpreted as meaning “at least one” or “one or more”), and the same applies to the use of definite articles used to introduce a claim description.
[0088] Furthermore, even if a claim explicitly states a specific numerical value introduced, a person skilled in the art will recognize that such a statement should generally be interpreted as meaning at least the stated numerical value (for example, a bare statement of "two statements" without other modifiers usually means at least two statements, or two or more statements).
[0089] Furthermore, when a convention similar to "at least one of A, B, and C" is used, such a configuration is generally intended to mean that a person skilled in the art will understand the convention (for example, "a system having at least one of A, B, and C" includes, but is not limited to, systems having only A, only B, only C, both A and B, both A and C, both B and C, and / or systems having both A, B and C). Those skilled in the art will further understand that, generally, disjunctive words and / or phrases that present two or more alternative terms should be understood, unless otherwise indicated in the context, in this specification, the claims, or the drawings, to be intended to include the possibility of one of the terms, either of the terms, or both of the terms. For example, the phrase "A or B" is generally understood to include the possibility of "A" or "B" or "A and B".
[0090] With respect to the attached claims, those skilled in the art will understand that the operations described herein may generally be performed in any order. Furthermore, while various operation flows are shown sequentially, it should be understood that the various operations may be performed in an order other than that illustrated, or may be performed simultaneously. Examples of such alternative orderings include, unless otherwise indicated by context, overlapping, interleaving, interrupting, rearranging, incrementing, preparing, supplementing, simultaneous, reverse, or other variant orderings. Moreover, terms such as “responding to,” “related to,” or other past tense adjectives are generally not intended to exclude such variants unless otherwise indicated by context.
[0091] Those skilled in the art will understand that the specific exemplary processes and / or apparatus and / or techniques described above represent more general processes and / or apparatus and / or techniques taught elsewhere in this Specification, for example, in the claims and / or other parts of this application filed with this Specification.
[0092] While various aspects and embodiments are disclosed herein, other aspects and embodiments will also be apparent to those skilled in the art. The various aspects and embodiments disclosed herein are for illustrative purposes only and are not intended to limit, and the true scope and spirit are indicated by the following claims.
[0093] The exemplary embodiments described in the detailed description, drawings, and claims are not limiting. Other embodiments may be utilized and other modifications may be made without departing from the spirit or scope of the subject matter presented herein.
[0094] Where a range of values is provided, unless otherwise explicitly indicated in the context, each intermediary value between the upper and lower limits of that range, up to one-tenth of the lower limit unit, and any other stated or intermediary values within that stated range are understood to be included in this disclosure. The upper and lower limits of these narrower ranges, which may be independently included in narrower ranges, are also included in this disclosure, but may be modified to any specifically excluded limits within the stated range. If the stated range includes one or both limits, the range excluding one or both of those included limits is also included in this disclosure.
[0095] Those skilled in the art will recognize that the components (e.g., operations), apparatus, objects, and accompanying discussions described herein are used as examples to clarify concepts, and that various configuration variations are conceivable. Therefore, when used herein, the specific examples and accompanying discussions described are intended to represent their more general class. In general, the use of any particular exemplary example is intended to represent its class and should not be construed as limiting it to excluding specific components (e.g., operations), apparatus, and objects.
[0096] Furthermore, any sequence and / or temporal order of a system and method described herein is illustrative and should not be construed as inherently limiting. Therefore, while process steps may be shown and described in sequence or temporal order, it should be understood that they are not necessarily limited to being performed in a specific sequence or temporal order. For example, steps in such a process or method may generally be performed in various different sequences and orders, while still within the scope of this disclosure.
[0097] Ultimately, the application publications and / or patents discussed herein are provided only for disclosures prior to the filing date of the described disclosure. Nothing in this specification should be construed as acknowledging that the described disclosure does not have prior rights to such publication by prior disclosure.
Claims
1. A sintered polycrystalline cubic boron nitride (PcBN) molded body, A hard phase containing cBN particles, present in an amount of 60% to 80% by volume based on the total volume of the sintered PcBN molded body, A ceramic bonding phase comprising an AlN phase, an Al₂O₃ phase, and at least one Co(x)W(y)B(z) toughening phase, present in an amount of 20% to 40% by volume based on the total volume of the sintered PcBN molded body, and Includes, A sintered polycrystalline cubic boron nitride (PcBN) molded body containing 3% to 6% by weight of aluminum, 0.9% to 2.5% by weight of cobalt, and 5% to 8% by weight of tungsten, where each weight percentage is based on the total weight of the sintered PcBN molded body.
2. The sintered PcBN molded body according to claim 1, wherein the ceramic bonding phase comprises quasi-stoichiometric titanium nitride (TiN), quasi-stoichiometric titanium carbonitride (TiCN), or a combination thereof.
3. The sintered PcBN molded body according to claim 1, wherein the ceramic bonding phase comprises quasi-stoichiometric or stoichiometric TiNO, quasi-stoichiometric or stoichiometric TiCNO, or a combination thereof.
4. The sintered PcBN molded body according to claim 1, wherein the cBN particles have a particle size in the range of 3 microns to 6 microns.
5. The sintered PcBN molded body according to claim 1, wherein the cBN particles have a particle size in the range of 2 microns to 4 microns.
6. The sintered PcBN molded body according to claim 1, wherein the Co particles have a particle size in the range of 0.1 microns to 1 micron.
7. The sintered PcBN molded article according to claim 1, wherein the tungsten carbide (WC) particles have a particle size in the range of 0.1 microns to 1 micron.
8. (x) is 1, (y) is 2, and (z) is 2, and at least one Co(x)W(y)B(z) tough phase is CoW 2 B 2 A sintered PcBN molded body according to claim 1, comprising:
9. The sintered PcBN molded body according to claim 1, wherein (x) is 1, (y) is 1, and (z) is 1, and at least one Co(x)W(y)B(z) tough phase comprises CoWB.
10. A method for producing a sintered polycrystalline cubic boron nitride (PcBN) molded body, The process involves grinding a powder mixture containing cBN particles, wherein the powder mixture, which includes a hard phase present at 60% to 80% by volume based on the total volume of the powder mixture and a ceramic bonding phase present at 20% to 40% by volume based on the total volume of the powder mixture, is ground with a grinder containing at least tungsten carbide (WC) and cobalt to form a powder blend and generate mill debris. Drying the powder blend, The powder blend is sintered under high pressure and high temperature (HPHT) conditions to form an AlN phase and Al in the ceramic bonding phase. 2 O 3 To form a phase and at least one Co(x)W(y)B(z) tough phase Includes, A method for manufacturing a sintered PcBN molded body, wherein aluminum is present in an amount of 3% to 6% by weight, cobalt is present in an amount of 0.9% to 2.5% by weight, and tungsten is present in an amount of 5% to 8% by weight, with each weight percentage being based on the total weight of the sintered PcBN molded body.
11. A method for producing a sintered PcBN molded article according to claim 10, wherein the ceramic bonding phase includes quasi-stoichiometric titanium nitride (TiN), quasi-stoichiometric titanium carbonitride (TiCN), or a combination thereof.
12. A method for producing a sintered PcBN molded article according to claim 10, wherein the ceramic bonding phase includes quasi-stoichiometric or stoichiometric TiNO, quasi-stoichiometric or stoichiometric TiCNO, or a combination thereof.
13. A method for producing a sintered PcBN molded article according to claim 10, wherein the cBN particles have a particle size in the range of 3 microns to 6 microns.
14. A method for producing a sintered PcBN molded article according to claim 10, wherein the cBN particles have a particle size in the range of 2 microns to 4 microns.
15. A method for producing a sintered PcBN molded article according to claim 10, wherein the Co particles have a particle size in the range of 0.1 microns to 1 micron.
16. A method for producing a sintered PcBN molded article according to claim 10, wherein the tungsten carbide (WC) particles in the mill debris have a particle size in the range of 0.1 microns to 1 micron.
17. A method for producing a sintered PcBN molded article according to claim 10, wherein drying the powder blend includes vacuum drying, air drying, freeze-drying, or spray drying.
18. A method for producing a sintered PcBN molded article according to claim 10, wherein the grinding is carried out using one or more solvents comprising ethanol, methanol, isopropanol, butanol, cyclohexanol, acetone, hexane, heptane, toluene, water, or any combination thereof as a grinding slurry of a powder blend.
19. A method for producing a sintered PcBN molded article according to claim 10, wherein the HPHT conditions include a pressure in the range of 4 gigapascals (GPa) to 8 GPa and a temperature in the range of 1100°C to 1800°C.
20. (x) is 1, (y) is 2, and (z) is 2, and at least one Co(x)W(y)B(z) tough phase is CoW 2 B 2 A method for producing a sintered PcBN molded article according to claim 10, including the method described above.
21. A method for producing a sintered PcBN molded article according to claim 10, wherein (x) is 1, (y) is 1, and (z) is 1, and at least one Co(x)W(y)B(z) tough phase comprises CoWB.
22. A method for producing a sintered PcBN molded article according to claim 10, further comprising drying the powder blend and then placing the powder blend into a heat-resistant metal cup.
23. A cutting tool comprising a sintered PcBN molded body as described in claim 1.
Citation Information
Patent Citations
Cbn sintered compact
JP2000044347A
Cubic bn sintered compact
JP2000044350A
Cubic boron nitride sintered body, method for producing same, and tool
WO2021192509A1